Determining The House Buyers Requirements For Green Homes In Malaysia - Ismail, Radzi (2012)
Green homes consist of six main elements, namely community design and planning, efficient usage of resources, use of alternative resources, natural system, protection and safety, and reusing and recycling approach. These elements form the many requirements of green homes among house buyers in Malaysia. As the major contributor to the global and local environmental negative impacts, environmentally conscious decisions on these elements can significantly contribute to the protection of environment. To realise this ambition in the Malaysian, there is a need to develop a green home assessment framework that could integrate community design and planning, efficiency usage of resources, use of alternative resources, natural system, protection and safety, reusing and recycling approach factors. This framework could answer a multitude of problems in building green homes in the Malaysian housing industry. The objectives of this study are to examine the relationships between green home factors and house buyers’ requirements of green homes and develop an assessment framework for green homes. A number of hypotheses have been used to understand the relationships between the green home aspects and house buyers’ requirements of green homes. A survey by means of self-administered questionnaires has been employed to collect the data. The research sample is house buyers attending property fairs in six states and one federal territory in Malaysia namely, Kedah, Penang, Kelantan, Melaka, Johor, Sabah and Kuala Lumpur. The respondents have been selected with the convenience sample technique. Out of 2600 questionnaires distributed, 1642 answered questionnaires have been returned, a response rate of 63 per cent.